Linguistic Cybercartography: Expanding the boundaries of language maps - Murasugi, K. (Kumiko) (2019)
Cybercartography, in particular its representation of multiple perspectives and user-centred collaborative approach, is an ideal platform for language mapping. ‘Multiple perspectives’ includes multiple user perspectives, data relations, data presentations, and media formats. The user-centred approach is particularly suited to mapping Indigenous languages, as it empowers individuals and communities to create their own maps. Language maps have traditionally focused on two types of information: the distribution of languages and language varieties within a specific geographic region, and variation in linguistic forms based on geographical factors. In this chapter, the definition of ‘language map’ is expanded from a representation of linguistic and geospatial information to a visualization tool for all types of linguistic information and relations. What all language maps have in common is the presence of three geographical concepts: place, way, and region (Couclelis, 1998).